2003
DOI: 10.1016/s1474-5151(03)00065-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Pacemaker Patients: A Single and Multidimensional Self-Rated Health Comparison Study

Abstract: Since implantation of the first permanent pacemaker in 1958, significant advances have been made in pacemaker technology. To date, however, health-related quality of life (HRQoL) in a large pacemaker population has not been investigated. With dwindling clinical resources, it is important to study HRQoL in a pacemaker population in a reliable and straightforward manner. This study aimed to determine and compare single and multidimensional self-rated health (SRH) in a pacemaker population in terms of sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
1
4
0
2
Order By: Relevance
“…Last, but not least, older patients had worse physical and emotional roles, social functioning, and pain. On the contrary, a prior study by Malm et al 28 showed a better QoL in individuals aged between 65 and 84 years, those who were cohabiting, those who had their own dwelling, and those who had a PM for three years or less. The elderly may better adapt to their disease as they have already worked, raised their families, or have lower expectations regarding their remaining lifespan.…”
Section: Discussionmentioning
confidence: 70%
“…Last, but not least, older patients had worse physical and emotional roles, social functioning, and pain. On the contrary, a prior study by Malm et al 28 showed a better QoL in individuals aged between 65 and 84 years, those who were cohabiting, those who had their own dwelling, and those who had a PM for three years or less. The elderly may better adapt to their disease as they have already worked, raised their families, or have lower expectations regarding their remaining lifespan.…”
Section: Discussionmentioning
confidence: 70%
“…There is a great deal of knowledge available today about the technical performance of pacemakers and the biophysical life of pacemaker patients (Brunner-La Rocca, Rickli, Weilenmann, Duru, & Candinas, 2000), but more information is needed regarding these individuals' own experiences of their life situation. Knowledge about the life situation of patients with pacemakers is largely based on measures using different life quality instruments from the perspective of the researcher (Malm, Svensson, Karlsson, & Fridlund, 2003). Beery, Sommers and Hall (2002) show in their qualitative study that the confidence female pacemaker patients have in pacemaker treatment is partially due to emotional feelings regarding the pacemaker.…”
Section: Introductionmentioning
confidence: 99%
“…2007). However, it is perhaps worth noting that many quality of life studies relating to pacemaker patients focus on physical aspects of quality of life, related to the impact of various pacing modes in treating underlying disease processes and providing improvements in distressing symptoms such as dizziness, breathlessness and syncope (see Malm et al. 2003 and Van Eck et al.…”
Section: Resultsmentioning
confidence: 99%